Integrating disability into equity-focused general education teacher preparation - Boardman, Alison G.; Schwarz, Vanessa Santiago; Sollenberger, Lydia (Frontiers in Education, 2024)
Most students with disabilities spend the majority of their school day in general education classrooms, yet most general education teachers do not feel prepared to meet the diverse learning and social and emotional needs of these students. A key to the enactment of evidence-informed practice for creating and supporting meaningful learning experiences for students with disabilities is the preparation of general education teachers. In this article, we conceptualize the key features of high-quality teacher preparation that support general education teachers to teach students with disabilities. We illustrate how these features have been addressed in one equity-focused elementary teacher education program and provide recommendations and questions to consider for teacher preparation programs and future research. Recommendations for teacher preparation include (1) naming disability in guiding principles and program documents, (2) examining ableism, (3) integrating universal design for learning, and (4) navigating policies and practices together within higher education.